Indonesian Trail Making Test: Analysis of Psychometric Properties, Effects of Demographic Variables, and Norms for Javanese Adults - Lucia Trisni Widhianingtanti; Gilles van Luijtelaar; Angela Oktavia Suryani; Yohana Ratrin Hestyanti; Augustina Sulastri (Faculty of Psychology, Universitas Gadjah Mada, 2022)
Trail Making Test (TMT) has been widely used in Indonesia as an Executive Function (EF) test, however, no studies reported validity and reliability of the test. In this study, we analyzed TMT’s psychometric properties, including reliability and validity, effect of demographic variables such as education, age, and sex on the TMT, and propose norm scores for the urban population of Java Island. Four hundred ninety persons (aged 16-80 years) with varying education levels participated in the study. Four additional EF tests (Digit Span, Five Point, phonemic Verbal Fluency, and Stroop) were administered. Principal Component Analysis was used to test whether the structure of TMT supported theoretical foundations of EF. The test-retest reliability was estimated in different samples (N = 50). Results suggest that education increased and age decreased the performance, however there were no differences between high school graduates and undergraduates in the age range 16-39 years. The intraclass correlation as a reliability measure showed good results (TMTA, rs=0.76; TMT B, rs= 0.86; TMT B-A, rs=0.74). The PCA revealed that the TMT, Digit Span, and Five Point scores loaded highly on one construct, while Stroop, phonemic Verbal Fluency, and errors on Five Point test loaded highly on other. It can be concluded that TMT is a valid neuropsychological instrument measuring EF with high reliability score and has high sensitivity for education, and age effects. The study also provides TMT Norms and cut-off scores for Javanese population between 16 and 39 years old with senior high school and undergraduate level of education.